GAGASAN PENGATURAN PENJATUHAN SANKSI PIDANA DENGAN BERORIENTASI PADA KORBAN - Harahap, Diah Ratu Sari; Suherman, Suherman; Aryanti R, Dwi (Jurnal Yuridis, 2014)
Human is social creature. Human always needs others in getting their needs. Human sometimes breaks the law. Indonesian positive law has regulated material law as well as formal law. Formal law in criminal that is called crimin al procedural law in Indonesia is Kitab Undang-Undang Hukum Acara Pidana. Beside that, criminal procedural rule is regulated in several special criminal material rule. Criminal procedural law now focuses to suspects. Victims are not too concerned. Police only need their report. Further, the interest of victims is not important anymore. In the end, the decision of the judge is not accommodate the victim?s suffering.